How Development of Assessment Instruments with Quizizz Paper Mode in Procedure Texts: a Discourse Analysis Study - Tarigan, Anna Juliana; Hadi, Wisman,; Lubis, M. Joharis (Journal of Pragmatics and Discourse Research, 2024)
This study addresses the need for more engaging assessment tools in Indonesian language lessons for Class VII students at SMP Negeri 2 Sibolangit. It aims to (1) Explore the process of developing assessment instruments using Quizizz paper mode for procedure text materials, (2) Assess the validity of the Quizizz-assisted assessment instrument, and (3) Evaluate its practicality in classroom settings. Following the Borg and Gall research and development model, the study involves eight stages, from data collection to dissemination. Data analysis combines quantitative insights from questionnaires with qualitative feedback from validators and users. Results indicate high validity ratings from assessment and design experts, alongside strong practicality ratings from educators and students, highlighting the effectiveness of the developed assessment tool. Moreover, the discourse analysis approach provides valuable insights into how the assessment instruments facilitate meaningful interactions and learning experiences in the classroom, suggesting broader implications for curriculum design and pedagogical practices.